Relational Work in Peer Advice in a Chinese Corporate Online Discussion Forum - Xiaoyan, Wang; Zhe, Feng (Sinología hispánica. China Studies Review, 2020)
Former studies on advice has been focused on health and educational settings either online or offline, where the advice-giver usually enjoys an advantageous power relationship with the advice-seeker. Studies of advice in Chinese discourse are no exception. Given the insufficiency of studies on advice given by peers of equity power relations in Chinese discourse and the necessity to investigate into relational aspects, this study explores peer advice given by coworkers in a Chinese corporate online discussion forum, analyzing the advising strategies and the relational work involved. Analysis of data shows that Chinese make use of direct advising strategies more often than either conventionally or non-conventionally indirect strategies. Further examination of peer advice texts indicates that people are doing various types of relational work in giving advice to others online: mock closeness, impoliteness, solidarity and non-politeness. This study may, hopefully, help to deepen our understanding of advice-giving and relational work in Chinese discourse, especially in online discourse.